If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -4y = -33 Solving x + -4y = -33 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4y' to each side of the equation. x + -4y + 4y = -33 + 4y Combine like terms: -4y + 4y = 0 x + 0 = -33 + 4y x = -33 + 4y Simplifying x = -33 + 4y
| -56=-4x | | 8x-9=60 | | 2x+17=22-x | | 10=6-3r+4r | | 1,2z+5,5=0.1z | | 5x^2+21=3-x^2 | | x/=5 | | 8(x+-8)=2x+8 | | 3x^2+125=-25 | | 3z+8=z | | d^2-d-5=0 | | x^2-3x^2=200 | | -5x+6=2(3x-8) | | 8(8x-8)=2x+8 | | -5x^2=80 | | 6x=4(2x-3) | | -3+3(m+6)= | | 3(2x+4)=2(7x-2) | | 19-2n= | | 1,2-y=y-0,2 | | 1/5x=-9 | | 2x-5=-x | | L+8=2L-20+3-4 | | 3(3x-6)=-36 | | x/7=91 | | 4e^3x=160 | | 1/3(2x-5)-2=x-2 | | 34-3y=10+y | | 5b+1=39 | | .0014=p-8.85*p^2 | | .394*12= | | 38=-3+5(x+6) |